The Influence of Family, Peers and Brand Image on the Decision to Study at Universitas Mahkota Tricom Unggul - Sihombing, Ester Hervina; Honkley, Tony; Tambunan, Debora; Nasib, Nasib; Husni, Calysta Thedrica (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This research aims to determine the role of family, the influence of peers and brand image on the decision to study at Universitas Mahkota Tricom Unggul. The population in the research is all students at the Medan Budisatrya Private Vocational School in the 2022-2023 academic year, totaling 100 people, while the sampling technique uses saturated sampling results, which means the entire population can be used as a research sample of 100 people. This type of research is quantitative research. Quantitative research is research that aims to determine the degree of relationship and pattern/form of influence between two or more variables, where with this research a theory will be built that functions to explain, predict and control a phenomenon. From the results of this research, it can be seen that campus promotions should also attract family interest so that they can influence someone in deciding to study at a university. The influence of peers also needs to be considered. This is also related to the experience of a person or alumni who experienced studying at a campus or college. Brand image also influences individual decisions in choosing to study at a campus or college at Universitas Mahkota Tricom Unggul.